Wet-etch Induced Changes in Impedance of Carbon Nanotube – Silicone Rubber Electrode Materials for Active Implants. (2016) - Tegtmeier, K.; Borrmann, F.; Doll, T.
Abstract: Carbon Nanotubes (CNTs) immersed in silicone rubber provide a flexible electrode material which may be used in the development of neuronal implants as replacement for currently used platinum wires and as electrode-nerve-interface. Neuronal cells thrive on CNTs[1] because their size is similar to the neurites extensions. Since immersion leads to completely insulated CNTs, wet etching using TBAF in combination with solvents has been established to regain the nanostructured surface and remove the insulation. Focusing on the electrical properties of the electrode-nerve-interface, electrochemical impedance spectroscopy (EIS) was performed on the samples surfaces. In scanning electron microscopic images (SEM) the reduction of silicone rubber on the CNTs surfaces was shown, while EIS shows decreased impedances compared to the unetched surface.